Partner Choice in Spontaneous Mitotic Recombination in Wild Type and Homologous Recombination Mutants of Candida albicans. Issue 11 (1st November 2019) - Bellido, Alberto; Ciudad, Toni; Hermosa, Belén; Andaluz, Encarnación; Forche, Anja; Larriba, Germán
Abstract: Candida albicans, the most common fungal pathogen, is a diploid with a genome that is rich in repeats and has high levels of heterozygosity. To study the role of different recombination pathways on direct-repeat recombination, we replaced either allele of the RAD52 gene (Chr6) with the URA -blaster cassette ( hisG-URA3-hisG ), measured rates of URA3 loss as resistance to 5-fluoroorotic acid (5FOA R ) and used CHEF Southern hybridization and SNP-RFLP analysis to identify recombination mechanisms and their frequency in wildtype and recombination mutants. FOA R rates varied little across different strain backgrounds. In contrast, the type and frequency of mechanisms underlying direct repeat recombination varied greatly. For example, wildtype, rad59 and lig4 strains all displayed a bias for URA3 loss via pop-out/deletion vs. inter-homolog recombination and this bias was reduced in rad51 mutants. In addition, in rad51 -derived 5FOA R strains direct repeat recombination was associated with ectopic translocation (5%), chromosome loss/truncation (14%) and inter-homolog recombination (6%). In the absence of RAD52, URA3 loss was mostly due to chromosome loss and truncation (80–90%), and the bias of retained allele frequency points to the presence of a recessive lethal allele on Chr6B. However, a few single-strand annealing (SSA)-like events were identified and these were independent of either Rad59 or Lig4. Finally, the specific sizes of Chr6 truncations suggest that the inserted URA-blaster could represent a fragile site.